2004
DOI: 10.1103/physreve.70.051706
|View full text |Cite
|
Sign up to set email alerts
|

Pretransitional fluctuations in the isotropic phase of a lyotropic chromonic liquid crystal

Abstract: We have studied isotropic-to-nematic pretransitional fluctuations in an aqueous solution of disodium cromoglycate (cromolyn) by static and dynamic light scattering. Cromolyn is a representative of lyotropic chromonic liquid crystals with building units being elongated rods formed by aggregates of disk-like molecules. By combining light-scattering and viscosity measurements we have determined the correlation length and relaxation time of the orientational order-parameter fluctuations and estimated the size of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 43 publications
8
53
0
Order By: Relevance
“…L z 25 nm, which compares well with a previous estimate 58 L ¼ 18 nm for the isotropic phase of the same concentration at 305 K (5 K above T ni ).…”
Section: A Elastic Constantssupporting
confidence: 79%
“…L z 25 nm, which compares well with a previous estimate 58 L ¼ 18 nm for the isotropic phase of the same concentration at 305 K (5 K above T ni ).…”
Section: A Elastic Constantssupporting
confidence: 79%
“…Ultimately, the experimenter will generate strong evidence "for" or "against" each microscopic model from which a microscopic understanding of the local micro-and nanoenvironment around the particles can be deduced. One interesting new opportunity is to study depletion due to lyotropic chromonic liquid crystals [83][84][85][86] wherein the underlying plank-like macromolecules stack to produce rod-like mesogens which in turn assemble into liquid crystalline phases; the present method offers a novel way to measure the average length and length distribution of the stacks. In principle, the measurement also offers a tool to probe the size, shape, and folding of proteins.…”
Section: In Place Of L and D In Equationmentioning
confidence: 99%
“…In addition to studying polymer solutions and aqueous electrolyte solutions we have investigated critical fluctuations in liquid crystals [22,76], crossover kinetics of asphaltene aggregation in hydrocarbon solutions [24], and dynamics of gel formation andbreakage in a biopolymer gel [66]. We have elucidated the nature of the mysterious blue-phase-111-isotropic critical point in a chiral liquid crystalline solution and shown that this critical point belongs to the same universality class as ordinary critical points in fluids [22].…”
Section: Fluctuations In Other Complex Fluidsmentioning
confidence: 99%
“…By combining lightscattering and viscosity measurements we have determined the correlation length and relaxation time of the orientational order-parameter fluctuations and shown that the pretransitional fluctuations are accompanied by elongation of the cromolyn aggregates [76].…”
Section: Fluctuations In Other Complex Fluidsmentioning
confidence: 99%